Extended epigenotype in a Rattus novergicus : toxoplasma gondii association - Vyas, Ajai (2015)
Several studies demonstrate that rats (Rattus novergicus) infected with protozoan parasite Toxoplasma gondii exhibit lesser fear to cat odors. This is thought to increase transmission of the parasite to its definitive hosts, i.e. cats. This is an example of extended phenotype where a gene of an organism allegedly creates a phenotype in another organism. We examined a possible proximate mechanism for this phenotype, describing an epigenetic change in arginine vasopressin gene in medial amygdala of male rats. Exogenously mimicking medial amygdala DNA hypomethylation resulted in reduction of fear to cat odors in uninfected animals, thus suggesting sufficiency. Systemic blockade of infection-induced DNA hypomethylation countermanded infection-induced behavioral change, thus suggesting necessity. This leads us to propose an epigenetic basis for this extended phenotype.